Academic and Career Advancement for Black Male Athletes at NCAA Division I Institutions. Issue 150 (June 2016) - Baker, Ashley R.; Hawkins, Billy J.
Abstract : This chapter examines the structural arrangements and challenges many Black male athletes encounter as a result of their use of sport for upward social mobility. Recommendations to enhance their preparation and advancement are provided.